Korelasi Efek Samping Antiepilepsi terhadap Ketaatan Pasien Epilepsi di RSUD Arifin Achmad Provinsi Riau - Fina Aryani; Lovina Aldelyn; Ratna Sari Dewi; Septi Muharni; Husnawati Husnawati (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Epilepsy is a disorder that is seen as a symptom due to disruption of electrical activity in the brain caused by various causes. Adherence is an important point in the management of epilepsy and suspected discomfort of side effects is a factor that supports adherence of epilepsy patients. The purpose of this study was to analyze the effect of the occurrence of side effects on the level of adherence in the treatment of epilepsy patients. This research was analytical descriptive observational with cross-sectional study. Data was collected by accidental sampling method by giving questionnaires directly to patients who met the inclusion criteria in Arifin Achmad Hospital of Riau Province. Samples are 31 outpatient epilepsy patients. The results showed that the side effects that often occur are headaches with percentages 38,7% and fatigue are 38.7% and 29% while patients with high adherence are 51.62% and low adherence is 48.38%. The results is no correlation between side effects and adherence of epilepsy patients (p = 0.144 and r = -0.269).